Economia compartilhada e compartilhamento do conhecimento : um estudo sobre as plataformas airbns e couchsurfing - Ziquinatti, Franciele Marques (2019)
Sharing knowledge has been an important factor in sharing economy platforms because of the influence they have on the decision-making of other individuals from sharing knowledge. However, recent evidence suggests that some users do not sharing knowledge. Therefore, this study aims to analyze why users sharing knowledge on sharing economy platforms in the area of tourism, specifically Airbnb and Couchsurfing. Aiming to meet this objective, this qualitative study began with the literature review, which defined seven categories for knowledge sharing. Afterwards, a netnography was performed to understand the context and individual interviews with 13 users of the platforms. The results point to two new categories for sharing knowledge on sharing economy platforms: a) contribution and b) feedback or feedback, as well as new views on categories of obligation, benefit, trust, and reward. This study helped to understand users' thinking by sharing knowledge on sharing economy platforms, specifically in the area of tourism. As limitations of the study, questions are related to the age range, social class and location of the research. In relation to future research, studies are suggested to compare the categories of knowledge sharing in emerging and rich countries, as well as in different areas and platforms of the sharing economy. Specifically for the Couchsurfing platform, a study should be carried out to identify if the verification of the user profile through the payment of a fee has an influence on the user's confidence in using the platform.